Peran Customer Online Review dalam Memediasi Niat Beli Produk Skincare - Yandi Suprapto; Golan Hasan; Feby (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the influence of digital marketing on purchase intention in the skincare industry, focusing on the role of social media marketing, e-WOM, brand image, and influencer endorsers mediated by customer online reviews. According to Statista (2020), the skincare industry experienced significant growth with a total value reaching USD 335.6 billion in 2020, increasing by 3.6% from the previous year and projected to reach USD 344.4 billion in 2021. This research aims to analyze the causal relationships between digital marketing variables (social media marketing, e-WOM, brand image, influencer endorsers) on purchase intention with customer online reviews as a mediating variable. The research method uses a quantitative approach with path analysis to test nine proposed hypotheses. The results show that SMM, e-WoM, and Brand Image have a significant influence on Customer Online Review, while Influencer Endorser shows no significant influence. This research extends previous studies by integrating the role of customer online reviews as a mediator in influencing consumer purchase intention